Detection of Beta–Human Papillomavirus in a Child With Polyomavirus-Associated Trichodysplasia Spinulosa. (December 2017) - Kadam, Pooja; Pan, Teddy; Gates, Rachelle; Rivetz, Jessica; Rady, Peter; Tyring, Stephen; Carlson, John A.
Abstract : Abstract: Viral associated trichodysplasia spinulosa (VATS) is a rare cutaneous eruption characterized by folliculocentric papules, keratin spicules, and alopecia associated with trichodysplasia spinulosa–associated polyomavirus (TSPyV) infection. We report a case of a 6-year-old male child who presented with a generalized papular eruption during chemotherapy for acute lymphoblastic leukemia. The papules were tested for human papillomavirus (HPV) DNA by nested polymerase chain reaction (PCR) and TSPyV using PCR and gene sequencing studies. The lesions were positive for TSPyV by PCR combined with sequencing and showed high copy number with real-time PCR, and beta-papillomavirus was identified by PCR and sequencing. Immunohistochemistry revealed inner root sheath keratinocytes expressing nuclear HPV L1 capsid antigen. To our knowledge, this is the first case of concomitant productive HPV and TSPyV infection in a VATS-affected patient. The presence of HPV may be coincidental, however, further studies are needed to establish whether specific HPV genotypes influence the development of abnormal inner root sheath trichohyalin granules found in VATS.